Аналіз методів керування безпілотними літальними апаратами - Микийчук М. М.; Зіганшин Н. С. (Видавництво Львівської політехніки, 2019)
Розвиток технологій із виробництва БПЛА (безпілотних літальних апаратів), крім експлуатаційних, правових та комерційних рішень, потребує стандартизації методів контролю як для наземних комплексів, так і для літальних апаратів та платформ. Інтернет-гіганти Google, Facebook протягом довгого часу підтримують стартапи із розвитку безпілотних літальних апаратів для різних сфер використання – від поставки товарів (від пошти до піци) до створення літальних платформ для забезпечення інтернетом регіонів, де неможливо розташувати наземні чи надводні станції. Збільшення кількості літальних апаратів потребує пошуку методів автономної навігації, способів утворення груп та мереж. Тому питання впровадження нових методів керування є актуальним. In addition to operational, legal and commercial solutions, the development of UAV (unmanned aerial vehicle) production technologies requires the standardization of control methods for both ground-based systems of aircrafts and platforms. Internet giants such as Google and Facebook continue to support the development of drone start-ups for various fields of use, from the delivery of goods (from mail to pizza) to the creation of flying platforms to provide the Internet in regions where it is impossible to locate ground or surface stations. Increasing the number of planes requires searching for autonomous navigation methods, methods of the group. Therefore, the issue of introducing new management methods is very important. Worldwide, robots are being built to create unmanned aerial systems as backbone elements of UAVs [1, 2, 3]. The priority is given to the information systems, the task of which is to monitor the surrounding space, the cost of which is much lower in comparison with piloted equipment. UAVs designed for the implementation of the monitoring task, the peculiarity of which should be provided in the development of unmanned aerial systems. As a consequence, it is necessary to use specialized techniques for their creation and use for each type of UAV. In order to implement the tasks set, it is necessary to develop the theoretical basis for the creation and use of unmanned aerial systems, which will ensure decision-making in the design and the effective use of these tasks and ensure their development. The development of such a theory is conditioned by the separation of modern unmanned aerial systems into a separate type of unmanned aerial vehicle. The main tasks of the UAVs include monitoring of surface, atmosphere and infrastructure objects, retransmission of radio signals, delivery and delivery of orders. One of the decisive advantages of using unmanned aerial vehicles is that they are more (than manned flying vehicles) that meet the criterion of cost-effectiveness and pose a risk to the lives of pilots. UAV-based complexes have low operating costs as compared to manned aeronautical equipment [4], due to the lack of costs for flight crew training [5]. Unmanned aerial complexes have only inherent properties, namely: use in case of impossibility of using manned aviation; lack of infrastructure, the threat of chemical, bacteriological and radioactive contamination. Unmanned aerial vehicles, including unmanned aerial vehicles, unmanned aerial, offshore and submarine stations, have great prospects for creating a smart city or a country network. The purpose of this work is to study the analysis of UAV control methods and their metrological support. Key words: UAV; Standardization; Control methods; Reliability analysis. Ключові слова: БПЛА; стандартизація; методи керування; аналіз надійності.
Analysis of unmanned aerial vehicles control methods